PERBEDAAN PENGARUH POVIDONE-IODINE 10% DAN CHLORHEXIDINE 0,2% TERHADAP PENINGKATAN JUMLAH OSTEOBLAS DAN KEPADATAN KOLAGEN PASCA PENCABUTAN GIGI (Studi Eksperimental pada cavia cobaya) - , Indria Nehriasari, drg M Masykur Rahmat, Sp BM (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tooth extraction can cause hard and soft tissue injury. Antiseptic solution can be used as an anfection control of infection because an infected wound can impede the healing process. Ten prosen Povidone-iodine (PI) and 0,2% Chlorhexidine (CHX) are an antiseptic solution with broadspectrum that can be well accepted by body which widely used in oral surgery clinic. Many researhers mention about cytotoxic effect of these two solutions on host cell culture. The aim of this research is to know the differences of 10% PI and 0,2% CHX by counting the osteoblast count and collagen thickness on guine pigs wound after tooth extraction. Fifty four guinea pigs were divided into 3 groups. After left lower incisor extraction, 10% PI, 0,2% CHX and saline as control, used as irigation solution on the tooth socket, 3 ml for 15 seconds everyday. Nine guinea pigs on each groups then underwent a surgery on day seventh and 14th. Guinea pig mandible were resected then histologic preparations were made furthermore stained with Hematoxillin-Eosin to watch the osteoblast count and Trichrom Mallory to watch the tipe I collagen thickness. Result of this research shows the 10% PI solution on wound healing process after extraction has higher osteoblast count than 0,2% CHX with a significant differenec (p<0,05) on day 7th and 14th and has thicker collagen on day 7th than 0,2 % CHX although not significant.